Effects of walnuts consumption on vascular endothelial function in humans: A systematic review and meta-analysis of randomized controlled trials. (December 2018) - Mohammadi-Sartang, Mohsen; Bellissimo, Nick; Totosy de Zepetnek, Julia O.; Bazyar, Hadi; Mahmoodi, Marzieh; Mazloom, Zohreh
Summary: Bachground and aims: Endothelial dysfunction can promote atherosclerosis pathogenesis. The aim of the present meta-analysis was to determine the effects of walnut consumption on peripheral endothelial function (EF) in adults. Methods: PUBMED, MEDLINE and EMBASE were searched to identify studies up to August 2017. Eligible studies conducted randomized controlled trials (RCTs) on the effects of walnut consumption compared with a control on EF. Standard mean difference (SMD) and 95% confidence intervals (CI) were reported as summary statistics. Standard methods were used for assessment of heterogeneity, meta-regression, sensitivity analysis and publication bias. Results: Five studies comprising a total of 323 subjects were included in the meta-analysis. The results showed a significant increase in EF after walnut consumption (SMD: 0.40%; 95% CI: 0.20 to 0.62; p < 0.001) with no evidence of heterogeneity across studies. Sensitivity analysis showed that the effect size was robust and not sensitive to any single study. Meta-regression did not indicate any significant association for an increase in EF after walnut consumption with dose of treatment, duration of treatment, or baseline EF. Conclusion: The available evidence from RCTs suggests there may be a clinically relevant effect of walnut consumption on EF.